2016
DOI: 10.1038/srep33423
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and low-volume point-of-care diagnostics on flexible strips – a study with cardiac troponin biomarkers

Abstract: We demonstrate a flexible, mechanically stable, and disposable electrochemical sensor platform for monitoring cardiac troponins through the detection and quantification of cardiac Troponin-T (cTnT). We designed and fabricated nanostructured zinc oxide (ZnO) sensing electrodes on flexible porous polyimide substrates. We demonstrate ultrasensitive detection is capable at very low sample volumes due to the confinement phenomenon of target species within the ZnO nanostructures leading to enhancement of biomolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Remarkably, the results obtained using this relatively cheap and simple fabrication method, are comparable or even outperform some of the recently reported flexible electrical devices based either on single MoS 2 flakes (2.2–10 mm) or chemical vapor deposition (CVD) grown (9–14 mm), and others fabricated in polyimide supports using various materials such as organic films (28 mm), silicon nanowires (7.5 mm), graphene (4 mm), or ZnO nanostructures (9 mm) …”
Section: Resultssupporting
confidence: 77%
“…Remarkably, the results obtained using this relatively cheap and simple fabrication method, are comparable or even outperform some of the recently reported flexible electrical devices based either on single MoS 2 flakes (2.2–10 mm) or chemical vapor deposition (CVD) grown (9–14 mm), and others fabricated in polyimide supports using various materials such as organic films (28 mm), silicon nanowires (7.5 mm), graphene (4 mm), or ZnO nanostructures (9 mm) …”
Section: Resultssupporting
confidence: 77%
“…Our chip-based LSPR cTnT biosensor provides a limit of detection (LOD) as low as 507 fg/L, which is 10 4 fold more sensitive than the commercial Elecys troponin T electrolumi-nescense immunoassay (ECLIA, 4 th generation, Roche Diagnostic) 18 and at least 50 fold lower than other label-free analytical techniques. 19,20 The initial LSPR biosensor work by the Chilkoti 21 and Van Duyne 13 groups demonstrated that in chip-based sensors, fabrication requires three important steps: (i) Immobilization of chemicallysynthesized/lithographically-fabricated nanoparticles onto suitable transparent solid substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated the application of ZnO as biosensors, i.e. in DNA immobilization [180], in glucose level detection [176,177,181], for cardiac biomarker detection [179,182,183] and also for cancer diagnostic [178,184,185].…”
Section: Zinc Oxidementioning
confidence: 99%